Enantioconvergent hydrolysis of racemic epoxides at elevated concentrations in Tween-20/phosphate buffer by the corresponding epoxide hydrolases. (April 2022) - Hu, Bochun; Zhu, Xiuxiu; Zhang, Dong; Lin, Wenqian; Wu, Mengdi; Wu, Minchen
Abstract: For effectively actualizing the gram-scale preparation of ( R )-phenyl-1, 2-ethanediol (PED) via the enantioconvergent hydrolysis of racemic ( rac -) styrene oxide (SO) at elevated concentration using whole-cell of E. coli / sleh2, the reaction media were constructed by adding non-ionic surfactants, organic solvents, and deep eutectic solvents into phosphate buffer, respectively. After screening, using conversion ratio ( c ) of rac -SO as the main criterion, the most suitable reaction medium, 30% (v/v) Tween-20/phosphate buffer (50 mM, pH 7.0), was identified, where the c of 400 mM rac -SO was elevated to > 99% from 62.1% in phosphate buffer. The scale-up enantioconvergent hydrolysis of 400 mM rac -SO was carried out in 50 mL Tween-20/aqueous buffer using 200 mg/mL wet cells of E. coli / sleh2 at 20 °C for 8 h, affording ( R )-PED with 96.2% ee p and 97.2% yield. The experimental results demonstrated that the identified medium can alleviate the inhibition of ( R )-PED on the EH activity of E. coli / sleh2 . Furthermore, this medium was also applied to the hydrolytic reactions of 300 mM rac-m -nitrostyrene oxide ( m NSO) and m -chlorostyrene oxide ( m CSO) using the corresponding E. coli / rpeh L360C and / pveh1 Z6, respectively. The c values of rac - m NSO and m CSO were increased to over 99% from 72.4% and 52.1% in phosphate buffer. Graphical Abstract: ga1 Highlights: Tween-20/buffer was rarely applied in enantioconvergent hydrolysis of rac -epoxides. The highest allowable concentration of rac -SO was elevated to 400 from 200 mM. Hydrolysis was performed affording ( R )-phenyl-1, 2-ethanediol with 96.2% ee p .